Ruled by Moloch - Shahverdyan, Gayane (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The problem of psychological and subjective well-being has been in the focus of psychologists for more than 50 years. Numerous studies have been conducted, and a huge number of factors correlated with well-being, have been discovered. However, these studies demonstrate a mechanical bаnk of correlations without having a holistic conceptual approach to the subject. The author hopes that similar studies will not be conducted in the next 150 years and also calls on psychologists to relate selectively to the material that is being taught to the students of the psychological faculties
Keywords: psychological well-being, subjective well-being, happiness, university education, diagnostic methods